2019
DOI: 10.1016/j.reth.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Novel hybrid three-dimensional artificial liver using human induced pluripotent stem cells and a rat decellularized liver scaffold

Abstract: Introduction Liver transplantation is currently the only curative therapy for end-stage liver failure; however, establishment of alternative treatments is required owing to the serious donor organ shortage. Here, we propose a novel model of hybrid three-dimensional artificial livers using both human induced pluripotent stem cells (hiPSCs) and a rat decellularized liver serving as a scaffold. Methods Rat liver harvesting and decellularization were performed as reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 19 publications
(33 reference statements)
0
34
0
1
Order By: Relevance
“…[88] These results suggest a regulatory role of endothelial cells, which is an important finding for this field. The iPSCs have also demonstrated their tissue-specific differentiation potential for regenerative strategies when cultured on decellularized matrices of livers, [92] lungs, [93,94] pancreas, [95] and human cardiac ECM. [96] The use of embryonic and/or pluripotent stem cells is of extreme importance for breakthrough advances in cell development and differentiation.…”
Section: Decellularized Ecm Guiding Tissue-specific Cellular Differentiationmentioning
confidence: 99%
“…[88] These results suggest a regulatory role of endothelial cells, which is an important finding for this field. The iPSCs have also demonstrated their tissue-specific differentiation potential for regenerative strategies when cultured on decellularized matrices of livers, [92] lungs, [93,94] pancreas, [95] and human cardiac ECM. [96] The use of embryonic and/or pluripotent stem cells is of extreme importance for breakthrough advances in cell development and differentiation.…”
Section: Decellularized Ecm Guiding Tissue-specific Cellular Differentiationmentioning
confidence: 99%
“…Different cell types could be used for repopulating decellularized livers, including primary hepatocytes, iPSCderived hepatocyte-like cells, stem cells, or mesenchymal stromal cells for recellularization of the parenchymal areas, and endothelial progenitor cells or human umbilical vein endothelial cells (HUVEC) for reendothelization [85,[128][129][130][131][132]. However, optimization of the recellularization process is still a challenge when more than one cell type per scaffold is used.…”
Section: Bioengineered Liver Scaffolds and Their Transplantationmentioning
confidence: 99%
“…One of these strategies is the transplantation of hepatocyte sheets onto the surface of mice livers [108]. Additionally, different scaffolds have been used to support hPSC-derived hepatocytes for subsequent transplantation, namely PCL fibers [109] and decellularized livers [110,111]. Besides this, a recent study reported for the first time, to the best of our knowledge, the use of current good manufacturing practice (cGMP)-compliant hepatocytes generated from hPSCs for transplantation [112].…”
Section: Regenerative Medicinementioning
confidence: 99%